(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article made a brief overview of creativity of Tolen Abdikov. We consider his own concept and image of the characters. Writer Tholen Abdikov contributed to the Kazakh prose as a writer-mystic, science fiction. The author of this article examines his characters from the perspective of the author. The author analyzes the views of well-known scientists about Abdikov creativity and express their views. The article made a thematic review of the writer’s contemporaries of Tolen Abdikov. This author demonstrates the importance and relevance of their research. Tolen Abdikov has its own important role in the history of the Kazakh prose. His personal views about people, about life discussed in this article, and determined it’s point of view. The author studies the style and features of creativity of Abdikov and showing its appreciation to the work of the writer.